1986
DOI: 10.1111/j.2042-7158.1986.tb04619.x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of nifedipine after multiple doses

Abstract: The single and multiple dose pharmacokinetics of oral nifedipine capsules, 10 mg, have been examined in five patients with peripheral vasospasm. After a single dose, nifedipine was rapidly absorbed in three and slowly absorbed in two patients. Mean bioavailability parameters included a tmax of 2.9 h, a Cmax of 33.3 ng ml-1 and a AUC0-8 h of 113.3 ng h ml-1. After multiple dosing with either 10 or 20 mg every 8 h for 10 days the mean tmax at steady state was 2.1 h while the mean dose-corrected (to 10 mg) Cmax a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…The remaining dose is excreted in the feces as metabolites resulting from biliary excretion. The reported total body clearance ranges from 450 to 700 mL/min, which concurs with the mean elimination rate constant of 0.173 h −1 …”
Section: Pharmacokinetic Propertiessupporting
confidence: 80%
See 3 more Smart Citations
“…The remaining dose is excreted in the feces as metabolites resulting from biliary excretion. The reported total body clearance ranges from 450 to 700 mL/min, which concurs with the mean elimination rate constant of 0.173 h −1 …”
Section: Pharmacokinetic Propertiessupporting
confidence: 80%
“…The study results are in agreement with the conclusions derived independently from another study reported by Raemsch and Sommer However, the validity of results cannot be considered conclusive as the duration of pharmacokinetic studies was limited to 5 days that may not adequately reflect the conditions of chronic treatment. In a separate study reported by Lesko et al, accumulation of nifedipine following the multiple dosing was observed particularly when the dosage strength was increased from 10 to 20 mg per intake in 8 h intervals.…”
Section: Pharmacokinetic Propertiesmentioning
confidence: 87%
See 2 more Smart Citations
“…When pharmacokinetic data were compared after oral administration of 20 mg nifedipine to healthy volunteers from Germany [9] and Japan [10], the Japanese subjects had significantly higher AUC and Cmax values [11]. Similarly, comparison of AUC data obtained in a number'of studies after the administration of either a single 10 mg capsule or a 20 mg slow release preparation to Caucasians [1, [12][13][14][15][16][17] and Mexican subjects [18][19][20] showed significantly higher AUC and Cmax values in the Mexicans.…”
mentioning
confidence: 99%